Optimization of culture condition for iaa roduction by Bacillus sp. Isolated from cassava field of Vietnam - Viet Cuong, Pham; Hoa, Nguyen Phuong (Vietnam Journal of Science and Technology, 2021)
Abstract. The bacteria capable producing IAA were isolated from roots of cassava growing in Tay Ninh region (Southern of Vietnam). The isolate producing highest amount of IAA was chosen for identification and optimization of culture conditions for IAA production. By analyzing 16S rRNA sequence, the selected isolate was identified as Bacillus sp. DTAN-M5. The influence of different parameters on IAA production of this strains was evaluated by “one factor at a time” method and the obtained results showed that the best conditions for IAA production of DTAN-M5 were medium with following components: 1% peptone; 0.5% sucrose , 0.6% yeast extract, 0.5% NaCl, pH 7.1, supplemented with 2mg/L L-tryptophan, incubation in a shaker 150 rpm at 30o C for 84 hours. The maximum amount of IAA was 84,13 µg/mL